Length Change of Shoe Last Footstep in Series - Gorbachik Vladimir; Bashkina Vladislava (Vestnik of Vitebsk State Technological University, 2018)
The article presents results of studies of changes in the parameters of shoe last footstep of women's shoes with a particularly high heel. The benchmark analysis of experimental and theoretical data of the change in the amount of shoe last (insole) footstep shear of the shoe in the heel part is made. The shear depends on shoe size and pitch.